Clinical, computed tomographic and histopathological findings in two cats with pulmonary fibrosis of unknown aetiology - Duffy, Eleanor C (JFMS Open Rep, 2020)
CASE SERIES SUMMARY: Two cats were presented for further investigation of respiratory signs. One cat had a history of a cough and the other, tachypnoea. In each case, thoracic CT was performed, which revealed a generalised marked reticular pattern in the first cat and focal consolidation of the right caudal lung lobe in the second cat. The first cat was euthanased following completion of the imaging study and a post-mortem examination was performed. The second cat underwent surgical excision of the abnormal lung lobe and survived for 4 years after diagnosis. Histopathology performed on lung tissue removed from each cat was consistent with pulmonary fibrosis. RELEVANCE AND NOVEL INFORMATION: This small case series adds to the existing literature and highlights the heterogeneous clinical course and variable appearance of pulmonary fibrosis on CT of affected cats. These cases provide evidence that pulmonary fibrosis in cats incorporates a wide spectrum of fibrotic lung disease and demonstrates the possibility for prolonged survival following diagnosis where disease is localised and amenable to surgical resection.